2013
DOI: 10.1007/978-3-642-39188-0_69
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Art with Brain Controlled Interface

Abstract: This essay presents experimental computer artworks using Brain Controlled Interface (BCI). It points to a preliminary contextualization and general development emphasizing affective, sensory, poetic and aesthetic experiences intermediated by mindware devices. BCI offers a new research art field using a low-cost neuro system to explore human mind's untapped potential. A BCI for a Java3D framework allowed to arrive at the concept of exoendogenous interactivity. The main contribution of this essay is the novel us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Pulse and oxygen in blood sensor, airflow sensor, body temperature sensor, electrocardiogram sensor, glucometer sensor, galvanic skin response sensor (GSR), blood pressure sensor (sphygmomanometer), and electromyography sensor (EMG), are some examples of the health sensors embedded in the smart-wearables. Some examples of smartwearables include Epoc Emotiv [6], an EEG headset capable of capturing brain signals that can be analysed to infer a user's thoughts, feelings, and emotions. MyoLink is another wearable that can continuously monitor the user's muscles and heart.…”
Section: Mobile Sensing For Healthcarementioning
confidence: 99%
“…Pulse and oxygen in blood sensor, airflow sensor, body temperature sensor, electrocardiogram sensor, glucometer sensor, galvanic skin response sensor (GSR), blood pressure sensor (sphygmomanometer), and electromyography sensor (EMG), are some examples of the health sensors embedded in the smart-wearables. Some examples of smartwearables include Epoc Emotiv [6], an EEG headset capable of capturing brain signals that can be analysed to infer a user's thoughts, feelings, and emotions. MyoLink is another wearable that can continuously monitor the user's muscles and heart.…”
Section: Mobile Sensing For Healthcarementioning
confidence: 99%
“…As far as this research is aware, the conglomeration of EEG & architectural research had only been prevalent within the recent decade with the earliest sited source in 2006 (Huang, 2006). The The few found recent studies (Mavros et al, 2012;Fraga et al, 2013;Kalogianni & Coyne, 2014;Shemesh et al, 2015;Mavros et al, 2016;Banaei et al, 2017;Coburn et al, 2017) are primarily concerned with EEG in its native biomedical & psychological context, an analytical tool aimed at analysing the human mental state. As a design tool, there had been one present example (Cutellic & Lotte, 2013), where EEG detected P300 signals, are used to recall supposed design interests.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The latter had a neural interface described in [3] by recent neuroscience research presented in [31], [32], artificial intelligence research shown in [1], [2], [21] and a Brain Computer Interface (BCI) discussed in [14], [33], [34] integrated with virtual reality software made possible by the use of a framework that has been in development since 2003. These factors have established the basis for the creation of this experimental and interactive artwork and the achieved solutions have allowed the emergence of a symbiosis-as described by David Norman [22] (p. 26)-where users' emotional states such as excitements and frustrations affect the virtual realms in the computer, thus creating slightly different configurations at each presentation of the artwork.…”
Section: The Application Numericvariationsmentioning
confidence: 99%